Characterization of polyvalent Escherichia phage Sa157lw for the biocontrol potential of Salmonella Typhimurium and Escherichia coli O157:H7 on contaminated mung bean seeds - Liao, Yen-Te; Zhang, Yujie; Salvador, Alexandra; Ho, Kan-Ju; Cooley, Michael B.; Wu, Vivian C. H. (Frontiers in Microbiology, 2022)
Seeds are one of the primary sources of contamination with foodborne pathogens, such as pathogenic E. coli, and various Salmonella serovars, for produce, particularly sprouts. Due to the susceptibility of sprout growth to chemical-based antimicrobials and the rising issue of antimicrobial resistance, developing innovative antimicrobial interventions is an urgent need. Therefore, the objective of this study was to characterize Escherichia phage Sa157lw (or Sa157lw) for the biocontrol potential of Salmonella Typhimurium and E. coli O157:H7 on contaminated mung bean seeds. Phage Sa157lw was subjected to whole-genome sequencing and biological characterization, including morphology, one-step growth curve, and stress stability tests. Later, antimicrobial activity was determined in vitro and upon application on the mung bean seeds artificially contaminated with E. coli O157:H7 or Salmonella Typhimurium. Sa157lw possessed a contractile tail and belonged to the Kuttervirus genus under the Ackermannviridae family, sharing a close evolutionary relationship with E. coli phage ECML-4 and Kuttervirus ViI; however, tail spike genes (ORF_102 and ORF_104) were the primary region of difference. Comparative genomics showed that Sa157lw encoded a cluster of tail spike genes—including ORF_101, ORF_102, and ORF_104—sharing high amino acid similarity with the counterfeits of various Salmonella phages. Additionally, Sa157lw harbored a unique tail fiber (ORF_103), possibly related to the receptors binding of O157 strains. The genomic evidence accounted for the polyvalent effects of Sa157lw against E. coli O157:H7 and various Salmonella serovars (Typhimurium, Enteritidis, Agona, Saintpaul, and Heidelberg). Furthermore, the phage did not contain any virulence, antibiotic-resistant, or lysogenic genes. Sa157lw had a 30-min latent period on both E. coli O157:H7 and Salmonella Typhimurium, with an estimated burst size of 130 and 220 PFU/CFU, respectively, and was stable at a wide range of temperatures (4C to 60C) and pH (pH4 to pH10). The phage application demonstrated a strong anti-E. coli O157:H7 and anti-Salmonella Typhimurium effects in 1.1 and 1.8 log reduction on the contaminated mung bean seeds after overnight storage at 22C. These findings provide valuable insights into the polyvalent Sa157lw as a potential biocontrol agent of Salmonella Typhimurium and E. coli O157:H7 on sprout seeds.